Determinanty motywacyjnego charakteru systemu oceniania pracowników - wybrane aspekty w świetle badań empirycznych - Chomątowska, Barbara (The determinants of motivational character of performance appraisal system - selected aspects, 2006)
There are many different ways of using the performance appraisal system for example: to make an administrative decisions, to change a remuneration, to identify training and development needs. The appraisal system can play very important functions in today’s organizations, such as informational, corrective and motivational function. This article concentrates on the motivational function of employees appraisal system – although it is closely linked with other functions. In order to achieve maximum benefit in this area we must recognize factors that influence motivational character of employees appraisal system. Therefore, the main aim of this article was to identify these factors. For example the theory and practice point to the appraisal interview (especially two way communication system between manager and employee during the interview) as the most important determinant of motivational character of the appraisal system. Result of research conducted by the author show that employees appraisal system can play vital function in the process of motivating of employees, but it can have negative as well as positive motivational consequences. Problem of motivating the employees by means of appraisal is constantly neglected in today’s organizations. For example appraisers are poorly trained in how to evaluate an employee’s performance (because of this lack of training, appraisers may make errors in their judgments).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 183-197